If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 5x + -2x + -4 = 49 Reorder the terms: -4 + 6x + 5x + -2x = 49 Combine like terms: 6x + 5x = 11x -4 + 11x + -2x = 49 Combine like terms: 11x + -2x = 9x -4 + 9x = 49 Solving -4 + 9x = 49 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 9x = 49 + 4 Combine like terms: -4 + 4 = 0 0 + 9x = 49 + 4 9x = 49 + 4 Combine like terms: 49 + 4 = 53 9x = 53 Divide each side by '9'. x = 5.888888889 Simplifying x = 5.888888889
| 15x*3= | | -12r-6=35 | | 3x^3-8x^2-4x=0 | | 3xa=a | | 2p+6=5 | | 8m=-120 | | 5r^2-48r+20=0 | | (14+6x)=134 | | (-15+4)n=77 | | 2-2=3 | | 4n+12=5n+7n | | y=2/3(-6)-2 | | y=2/3(6)-2 | | 25r^2-64=0 | | y=-2/3(6)-2 | | 124+x=25-3 | | y=-2/3(3)-2 | | y=-2/3(0)-2 | | y=-2/3(-3)-2 | | y=-3/2(4)+7 | | y=-3/2(2)+7 | | 4/14=q/12 | | 5/1-x=4/3-x | | y=-3/2(0)+7 | | y=-3/2(-2)+7 | | 5(8-2x)=40 | | -2x+2x+1=9 | | y=3/2(0)+7 | | 2q=0 | | 36k^2+12k+1=0 | | y=3/2(-2)+7 | | 4(u+1)=-4u+28 |